A case of multisystem inflammatory syndrome in children presenting as systemic onset juvenile idiopathic arthritis - Nadia Waheed; Nighat Haider; Jai Krishin (Journal of the Pakistan Medical Association, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a rare and serious COVID 19 manifestation characterized by generalized inflammatory response including inflammation of heart, blood vessels, lungs, kidneys, brain, skin, eyes and gastrointestinal system. Children usually present with fever lasting for 24 hours or more along with other symptoms like abdominal pain, vomiting, diarrhea, skin rash, red eyes and swelling of the lips, tongue, hands and feet. The children with MIS-C usually have negative results for a current infection with the COVID-19 but positive antibody results indicating these children were infected with the COVID-19 virus in the past. We present 12 months old girl with multisystem inflammatory syndrome presenting as systemic onset juvenile idiopathic arthritis (SOJIA) and positive COVID-19 PCR, she was treated successfully with dexamethasone and naproxen. Continuous